Optimalisasi Potensi Lahan Pertanian Untuk Ketahanan Pangan di Kecamatan Panceng, Gresik, Jawa Timur - Ana Toni Roby Candra Yudha; Abdul Mu’izz (Journal of Economics Development Issues, 2020)
Indonesia was known as an agrarian country, a country that has economic fundamentals based on agriculture, including all of regions in Java island. For example Gresik as one of the regions in the territory of East Java province. The aims of study is to find out, study and develop alternative policies regarding efforts to optimize the potential of agricultural land used for food. This study uses qualitative in phenomenology approaches. That is, research conducted with observations for more than a year settled in the location to study and formulate proposals for problems that arise in the object of the research location. The results of this study showed that, land in Panceng-Gresik regency which incidentally is associated with pond land, apparently by the local community most of it is actually processed as agricultural land oriented to mango, banana, and ‘palawija’. Among 1000m2 there are 80 percent of which is used for agricultural land needs, and this helps in the local economic rotation of the local village. Suggestions that are consistent with the results of the study are the need for detailed and quantitative identification of land, as well as business preferences and planted crops. This needs to be done to improve the productivity of crops and the farmer’s welfare.